Predictors of Helping Babies Breathe knowledge and skills among nurses in primary health settings in Dodoma region, Tanzania - Angelina A. Joho; Stephen M. Kibusi; Ipyana Mwampagatwa (BMC, 2020)
Abstract Background Globally, birth asphyxia is one of the leading causes of neonatal death. In Tanzania, neonatal deaths are estimated to be 25 deaths per 1000 live births and birth asphyxia accounts for 31% of those deaths. Method A cross-sectional study was conducted in 40 health centers within 7 districts in Dodoma Region among nurses working in maternity units. Simple random sampling was used to select participants. A knowledge questionnaire and performance skills checklist were used to assess nurses' knowledge and skills respectively. Chi-square and binary logistic regression were employed to test association and identify significant predictors of HBB knowledge and skills. Results A total of 172 participants completed the study out of 176 recruited. This represents a respondent rate of 98%. Findings indicate that age, duration of professional training, and experience in maternity were significant predictors for knowledge and skills. However, after control of the confounders, experience in the maternity unit was found to be the only significant predictor of knowledge and skills in resuscitation of the neonates (AOR = 2.94; CI: 0.96-8.98; P = 0.05) and (AOR = 4.14; CI: 1.12-15.31; P = 0.03) respectively. Nurses with longer maternity nursing care experience of 5 years and above were better able to answer questions that demonstrated adequate knowledge (53.9%) and perform skills correctly (53.2%) related to HBB. Those with less than 5 years' experience had limited knowledge (20%) and skills (10.5%). Conclusion In this setting, direct work experience in the maternity unit was the main factor influencing knowledge and skills in neonatal resuscitation with HBB.